Emotional stability as a key competence of managers - Tolstoukhova, I. V. (2018)
The paper substantiates the psychological structure of emotional stability as a key competence of managers, including three interrelated components (cognitive, emotional-motivational, practical). On the basis of the competence approach, the criteria for the formation of this concept are proposed and disclosed. The content of the constituent elements of emotional stability as a key competence is specified. During the study, the following methods were used: theoretical (analytical-synthetic, comparative, modeling method); empirical (stating experiment, observation, method of expert assessments, testing). The diagnostic program revealed three levels of development of emotional stability: high, medium, low. Identified in the course of the study, the components and criteria for the level manifestation of emotional stability as the key competence of future managers were the basis for creating the author's course «Psychology of emotional development». The results of the study can be used in the planning and preparation of lectures and seminars of academic disciplines of the humanitarian cycle.